ACCOUNT OF RENTAL RELATIONS IN PUBLIC SECTOR SUBJECTS (Web of Technology: Multidimensional Research Journal, 2024)
This article discusses the process of leasing fixed assets and lease relations in public sector entities and analyzes this process. It is discussed about the normative basis of accounting of the income of the state sector entities from the rental of fixed assets and their distribution. Proposals and recommendations were given regarding the existing problems in keeping the account of the lease of fixed assets in the public sector entities and their elimination.